Phenotypes in inflammatory bowel disease - Torres, Joana Maria Tinoco da Silva (2018)
Inflammatory bowel diseases represent a group of chronic conditions characterized by relapsing inflammation within the gastrointestinal tract. Crohn's disease and Ulcerative colitis are the 2 major forms of idiopathic inflammatory bowel disease. IBD is an extremely heterogeneous disease in what regards disease presentation, course and prognosis. The coexistence of other diseases may influence IBD´s clinical course. For example, patients with concomitant IBD and primary sclerosing cholangitis (PSC) have a distinctive phenotype, with milder colonic disease activity, more right-sided inflammation, more extensive disease and higher incidence of colorectal neoplasia. Furthermore, the coexistence of IBD bears a poor prognosis in PSC, increasing the risk of hepatobiliary malignancy, need for liver transplant or death. The reason for this distinctive phenotype is unknown, but a deeper understanding of the mechanisms underlying it could provide further insights into disease pathogenesis. PSC is an obstructive cholestatic disease associated with changes in the bile acid pool. Therefore, bile acids (BA) and BA receptors could play a hypothetical role. BA homeostasis is tightly regulated by the activation of BA receptors expressed in the intestine. The interaction between BA and their intestinal receptors has been shown to play a key role not only in enterohepatic circulation, but also in the regulation of inflammatory liver and intestinal responses, intestinal barrier function and antibacterial defense. Furthermore, the reciprocal interaction between BA and gut flora in the intestine may be of relevance in the context of IBD, where an imbalance between the protective and harmful bacteria (dysbiosis) has been demonstrated. Altogether, these data suggest that in PSC-IBD patients, the gutliver axis could be involved and contribute to disease phenotype. The goal of this project is to provide new insights into this special phenotype, focusing on the interactions between BA, BA receptors, and microbiome, and studying specific aspects of the natural history of patients with PSC-IBD. We started by studying the expression of the main bile acid receptor (FXR) in PSC-IBD versus IBD alone, and its relationship with inflammation, dysplasia and location in the colon. We observed that FXR expression is inversely correlated with neoplastic progression and severity of inflammation in UC. Furthermore, patients with PSC-UC had diminished FXR expression in the proximal colon compared to UC patients. This finding could contribute to the higher risk of proximal neoplasia in PSC patients. Recognizing the involvement of FXR in the control of inflammation and bacterial responses in the gut, and the important role of the gut microbiome in the pathogenesis of IBD, we next explored the differences in the mucosa-associated and stool-associated microbiota in PSCIBD versus IBD alone. Our first work in this area compared the mucosa-associated microbiome between PSC-IBD and IBD alone patients, in different locations in the colon. Biopsies taken during surveillance colonoscopy from the terminal ileum, right and left colon from patients with PSC-IBD, IBD alone and healthy volunteers were collected and sequenced using 16s rRNA for the study of the microbiome. We observed that the overall microbiome profile was similar across multiple locations in the gut from the same individual regardless of disease status, and therefore the phenotypic differences observed between PSCIBD and IBD alone in the right versus the left colon are not explained by variations in the gut microbiome alone. We also showed that the mucosa associated-microbiome of PSC patients was characterized by an enrichment of bacteria known to be involved in bile acid handling, and gut homeostasis, therefore suggesting indeed a role of gut flora in PSC-IBD’s special phenotype. Motivated by these findings we then sought to explore the correlations between stool microbiome and bile acid profile. For this study, we recruited Portuguese patients with PSCIBD and IBD alone patients. All patients had extensive colitis. From each patient demographic and clinical information as well as disease clinical and endoscopic activity scores were recorded. Each patient conducted a food-frequency questionnaire and nutritional analysis as well. In this study patients collected a paired fasting stool and serum sample for bile acid analysis. The stool sample was also studied and analyzed with 16S sequencing for the characterization of the gut microbiota. In this study, we observed that patients with PSCIBD had distinct microbiota and microbiota-stool BA correlations as compared to IBD alone. Interestingly, one of the taxa enriched in PSC-IBD in this study was the Fusobacterium genus, a taxon known to be involved in colorectal cancer. Finally, we wanted to study two very clinical and important questions in the management of patients with PSC-IBD: the rates of colorectal neoplasia in PSC-IBD in the current ear of improved endoscopic surveillance, and the fate of low-grade dysplasia. These are very important questions from the clinical standpoint since there is an increasing tendency to manage low-grade dysplasia in IBD in a conservative way with increased surveillance, since the progression to high-grade dysplasia and colorectal cancer seems to be infrequent. However, whether this premise was true for PSC-IBD as well remained to be defined. Therefore, we conducted a multicentre study on almost 300 patients with PSC-IBD and 1600 patients with IBD alone and considered their longitudinal endoscopic and pathological data. We confirmed that PSC remains a strong independent risk factor for aCRN in IBD. Furthermore, we observed that there is a faster progression to advanced colorectal neoplasia, highlight the peculiarities of PSC-IBD´s special phenotype. Therefore, our findings add further credence to current recommendations for careful annual colonoscopic surveillance in this high-risk population and consideration of colectomy once LGD is detected. It is evident that the cross talk between the liver and the colon in PSC-IBD patients, is worth exploring as it can provide important pieces of information that could lead to the development of new strategies in the management of this disease.